An experimental investigation of adaptive servo control of a single axis table - Özel, F. İlkin. (Thesis (M.S)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1992., 1992)
The object of this thesis is to model a dc motor driven single axis table system and to perform adaptive velocity and position control of the table. After modeling the system, in the first part of the thesis, fixed parameter and adaptive PI control of the velocity of the table has been achieved and the effects of several effective parameters in adaptive control such as initial estimates, initial covariance matrix and forgetting factor have been investigated. Recursive least squares estimation method has been used to estimate the system parameters at each step. The experimental results have shown that for speed control of a dc motor driven single axis table system, implementing adaptive control algorithm is better solution. In the second part of the thesis, the ordinary PO and adaptive pole assignment position control. of the table were performed. The effect of estimator parameters on the estimator and controller response has been examined. The results revealed that the adaptive regulator is advantageous over the ordinary PO pole assignment algorithm.
Keywords: Adaptive control systems.; Self-organizing systems.